The Structure of a Legal Norm System - Ziembiński, Zygmunt (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The paper is an English translation of a part of Problemy podstawowe prawoznawstwa published originally in 1982. The text is published as a part of a section of the Adam Mickiewicz University devoted to the achievements of the Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.